12a^2+b^3+6a^2b^4-18a^3b^2因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 18:53:21
18b(a-b)平方-12(a-b)立方=6(a-b)^2[3b-2(a-b)]=6(a-b)^2(3b-2a+2b)=6(a-b)^2(5b-2a)第一到第二步的理由18b(a-b)平方-12(a-
计算,A/2+(A/6+B)+(A/12+2B)+(A/20+3B)+.+(A/380+18B)(A=20B=10)计算,A/2+(A/6+B)+(A/12+2B)+(A/20+3B)+.+(A/38
因式分解18(a+b)^3-12b(b-a)^2因式分解18(a+b)^3-12b(b-a)^2因式分解18(a+b)^3-12b(b-a)^218(a+b)^3-12b(b-a)^2=18(a^3+
(a+2b)(2a+4b)(3a+6b)(4a+8b)(a+2b)(2a+4b)(3a+6b)(4a+8b)(a+2b)(2a+4b)(3a+6b)(4a+8b)=24*(a+2b)^4
(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程 (a-b)^6*[-4(b-a)^3]*
A-BA+B2B+A3A-B6A+2BA-BA+B2B+A3A-B6A+2BA-BA+B2B+A3A-B6A+2B(A-B)(A+B)(2B+A)(3A-B)(6A+2B)=(A-B)(A+B)(2B
用行列式的性质证明abbbaa+ba+2ba+3ba2a+b3a+3b4a+6b=a的四次方a3a+b6a+4b10a+10b用行列式的性质证明abbbaa+ba+2ba+3ba2a+b3a+3b4a
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程2(a+b)-[4(a+b)-3(a+b)]
若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=().若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=().若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=(
(12a^4b^5-4a^8b^3-6a^2b^3)/2a^2b^3(12a^4b^5-4a^8b^3-6a^2b^3)/2a^2b^3(12a^4b^5-4a^8b^3-6a^2b^3)/2a^2b
2a-{7b+[4a-7b-(2a-6a-4b)]-3a2a-{7b+[4a-7b-(2a-6a-4b)]-3a2a-{7b+[4a-7b-(2a-6a-4b)]-3a2a-{7b+[4a-7b-(2
18ab(a-b)^2-12a(b-a)^318ab(a-b)^2-12a(b-a)^318ab(a-b)^2-12a(b-a)^318ab(a-b)^2-12a(b-a)^3=18ab(a-b)^2
[-(a^2b)^2]^3*(12a^3b^4-6a^2b^3)=()[-(a^2b)^2]^3*(12a^3b^4-6a^2b^3)=()[-(a^2b)^2]^3*(12a^3b^4-6a^2b^
1(2a+b)b-(2a+b)(a+b)+2(a-2b)a26a^3b(a-b)^3-4ab^3(b-a)^22(a^2+b^2)(a+b)^2-(a^2-b^2)^21(2a+b)b-(2a+b)(
因式分解:3b(b-a)+6a(a-b)^2因式分解:3b(b-a)+6a(a-b)^2因式分解:3b(b-a)+6a(a-b)^23b(b-a)+6a(a-b)^2=3b(b-a)+6a(b-a)&
(-4a^6-20a^4b^2-12a^3b+6a^3b^2)/[-(-2a)^3](-4a^6-20a^4b^2-12a^3b+6a^3b^2)/[-(-2a)^3](-4a^6-20a^4b^2-
(-4a^6-20a^4b^2-12a^3b+6a^3b^2)/[-(-2a)^3](-4a^6-20a^4b^2-12a^3b+6a^3b^2)/[-(-2a)^3](-4a^6-20a^4b^2-
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)(a+2b)(a-2b)+(a-b)(a+b)-2(a-
已知2(a×a)+3(b×b×b)-5=0,则4a×a+6b×b×b+12=?已知2(a×a)+3(b×b×b)-5=0,则4a×a+6b×b×b+12=?已知2(a×a)+3(b×b×b)-5=0,
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*